Profesionalisme Kiai dalam Pengelolaan Pondok Pesantren dalam Konteks Kemodernan - Abd. Muqit (Jurnal Pendidikan Islam Indonesia, 2018)
The islamic boarding education forming of dormitory formed community under the leadership of Kyai, assisted by anyone or several ustadz (teachers) who lived area of Santri, and Mosques or Surau are as the center of education and worship, a study room as a means of teaching and learning activities as well as cottage as the residence of the santri. Educational activities are organized according to the Pesantren's rules and based on the principle of religion. In the era of reformation, openness and globalization, in order to maintain the quality of pesantren output, it was imperative that the leadership of Pesantren should be prioritized professionalism so that the implementation of pesantren education which leaded to quality assurance of graduates was always maintained, and throughout the period expected Pesantren continue to be able to produce a generation that can be existed acting in various life of society.